Peran pondok pesantren dalam integrasi nilai-nilai Islam dengan tradisi dan budaya lokal di Indonesia - Khasanah, Wardatul (Maliki Interdisciplinary Journal, 2025)
Islamic boarding schools are often considered traditional educational institutions that are less responsive to current developments, so they are considered less competent in the modern educational era, especially in the cultural and moral aspects of the next generation. This research aims to explore the extent to which Islamic boarding schools contribute to today's education. By using qualitative descriptive methods and library research, this research concludes several important things. First, the history of Islamic boarding schools shows that this institution has produced many influential kiai who play a significant role in the social order in Indonesia. Second, Islamic boarding schools which have become part of local cultural traditions have succeeded in developing intellectual platforms through various educational mechanisms, including teaching the Koran, hadith and classical books. Third, in the face of changing times, the pattern of education in Islamic boarding schools has undergone a transformation from traditional to more modern, although there are still Islamic boarding schools that maintain their traditional methods.